A novel mutation in the CYP27A1 gene in a family with cerebrotendinous xanthomatosis. (2nd October 2020) - Tang, Yi; Liu, Yanqiu; Li, Dan; Guo, Dongmei; Xing, Yi
Abstract: Purpose of the study: Cerebrotendinous xanthomatosis (CTX) is an inherited disorder associated with abnormal deposition of cholestenol in the brain and other tissues. Here we report a Chinese family with two affected members of CTX. Materials and Methods: Clinical data were collected. Gene analysis, MRI, neuropsychological assessments, and the biopsy of right Achilles tendon xanthoma were carried out. Results: The two cases had similar symptoms for cataracts, chronic diarrhea, progressive cognitive impairment and a disturbance of gait, and were identified with the same compound heterozygous mutations, c.435G>T in exon 2 and c.562C>T in exon 3. Conclusions: Cerebrotendinous xanthomatosis (CTX) is an inherited disorder associated with abnormal deposition of cholestenol in the brain and other tissues. Although CTX is a treatable disease, the time of beginning treatment is crucial for therapeutic effect. Unfortunately, it usually takes years even decades from initial symptoms to the diagnosis of CTX. The screening for 27-hydroxylase (CYP27A1) gene even before the occurrence of tendon xanthoma is important for early diagnosis.